2008
DOI: 10.1080/00016340701714703
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and genital DNA prevalence of HPV types 6, 11, 16 and 18 in a cohort of young Norwegian women: study design and cohort characteristics

Abstract: Given the high prevalence of HPV infection among young women with mostly single-type infection, and the fact that type-specific HPV screening is not recommended prior to the administration of the quadrivalent HPV vaccine, our data suggest the importance of widespread,rather than targeted, immunisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 24 publications
6
27
2
Order By: Relevance
“…There is recent evidence that ELISA is a lesssensitive method than the bead-based multiplex assay used in our study (Waterboer et al, 2005). In general, we can conclude that the baseline seroprevalence figures for all HPV types in our study were higher than reported previously (Lehtinen et al, 2006;Rama et al, 2006;Jit et al, 2007;Skjeldestad et al, 2008;Wang et al, 2008). When the more stringent (400 MFI) cut-off value for L1 antibodies was used, seroprevalence declined by [15][16][17][18][19][20]in particular,seroprevalence of HPV 16 (20 %) and HPV 18 (8 %) was in line with earlier reports (Viscidi et al, 1997;af Geijersstam et al, 1998;Stone et al, 2002).…”
Section: S Syrjä Nen and Others 1522contrasting
confidence: 55%
See 2 more Smart Citations
“…There is recent evidence that ELISA is a lesssensitive method than the bead-based multiplex assay used in our study (Waterboer et al, 2005). In general, we can conclude that the baseline seroprevalence figures for all HPV types in our study were higher than reported previously (Lehtinen et al, 2006;Rama et al, 2006;Jit et al, 2007;Skjeldestad et al, 2008;Wang et al, 2008). When the more stringent (400 MFI) cut-off value for L1 antibodies was used, seroprevalence declined by [15][16][17][18][19][20]in particular,seroprevalence of HPV 16 (20 %) and HPV 18 (8 %) was in line with earlier reports (Viscidi et al, 1997;af Geijersstam et al, 1998;Stone et al, 2002).…”
Section: S Syrjä Nen and Others 1522contrasting
confidence: 55%
“…In addition, abnormal cytology could not be correlated with positive serology (Rama et al, 2006). In the literature, HPV 16 seroprevalence in the healthy female population seems to vary from 3.4 to 44.0 % (af Geijersstam et al, 1998;Stone et al, 2002;Wang et al, 2003;Lehtinen et al, 2006;Villa et al, 2006;Marais et al, 2007;Skjeldestad et al, 2008;Wang et al, 2008). Seroprevalence seems to be more common among cervical intraepithelial neoplasia or sexually transmitted disease (STD) patients, as well as among women with cervical cancer or human immunodeficiency virus infection (Thompson et al, 2004;Viscidi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of HPV seroprevalence studies have been carried out in women from high-resource countries (3,6,(8)(9)(10)(11)(12)(13)(14). Few studies have focused on low-resource areas, such as Central and South America (7,(15)(16)(17), Asia (5,18) or Africa (19), where the highest HPV DNA prevalence in the world can be found, notably among middleaged women (20).…”
Section: Introductionmentioning
confidence: 99%
“…Prior infection with HPV does not provide women with adequate immunity against subsequent infections. In fact, serum antibody levels after natural HPV infection when detectable are low and 40-50% of women do not develop measurable antibody response after HPV natural infection (Viscidi et al, 2004;Nonnenmacher et al, 1995;Park et al, 1998;Heim et al, 2002;Skjeldestad et al, 2008). Moreover, it has been shown that an infection with a specific genotype does not decrease the probability of being infected by a phylogenetically-related genotype (Thomas et al, 2000).…”
Section: Prevalence Incidence Duration Co-infection and Re-infectionmentioning
confidence: 99%